2006
DOI: 10.1007/s10705-006-9025-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling in an Irrigated Wheat System in Sonora, Mexico: Measurements and Modeling

Abstract: An improved version of an ecosystem nitrogen cycling model (NLOSS) is described, tested, and used to analyze nitrogen cycling in the Yaqui Valley, Sonora, Mexico. In addition to previously described modules in NLOSS that simulate soil water and solute fluxes, soil evaporation, soil energy balance, and denitrification, modules were added to estimate crop growth, soil carbon cycling, urea hydrolysis, and nitrification. We first tested the model against season-long measurements of soil NO 3 -, NO 2 -, and NH 4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The weather, precipitation, irrigation, soil conditions, crop type (wheat, maize, bean (Phaseolus vulgaris L.), and yield information were also entered. Table 1 has some of the study information that was entered into the tool assessment, and detailed information about these studies can be found in Christensen et al (2006), Riley et al (2001), Grajeda-Cabrera et al (2004), Limon-Ortega et al (2008 and Govaerts et al (2006). The studies were used to assess the capability of the tool to estimate aboveground crop N uptake, system N use efficiency and N 2 O emissions.…”
Section: Methodsmentioning
confidence: 99%
“…The weather, precipitation, irrigation, soil conditions, crop type (wheat, maize, bean (Phaseolus vulgaris L.), and yield information were also entered. Table 1 has some of the study information that was entered into the tool assessment, and detailed information about these studies can be found in Christensen et al (2006), Riley et al (2001), Grajeda-Cabrera et al (2004), Limon-Ortega et al (2008 and Govaerts et al (2006). The studies were used to assess the capability of the tool to estimate aboveground crop N uptake, system N use efficiency and N 2 O emissions.…”
Section: Methodsmentioning
confidence: 99%
“…The price of water is often subsidized in irrigated systems, and farmers in these systems often apply an excessive amount of N to guarantee a high yield (Christensen et al 2006;Lobell and Ortiz-Monasterio 2006;Lobell et al 2004). This approach is different from rainfed farmers of Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers in irrigated regions do not follow this type of risk-averse behavior as strongly as under rainfed conditions. Rather, irrigation farmers tend to over-fertilize to guarantee the highest achievable yields using fertilizer subsidies (Christensen et al 2006;Lobell and Ortiz-Monasterio 2006;Lobell et al 2004). For that reason, in the FIS we assumed farmers optimized the N fertilizer application in situations where the net returns equal zero.…”
Section: Economic Analysismentioning
confidence: 99%
“…The Yaqui Valley in north‐western Mexico represents one of the world's largest wheat‐growing systems under irrigation and has conditions similar to the Indian and Pakistani Punjab and the Nile Valley in Egypt. Nitrogen application is indispensable in intensive, irrigated cropping systems, but the application of mineral N fertilizer is often inefficient, leading to a N use efficiency (NUE) of only 31% in the Yaqui Valley (Ortiz‐Monasterio & Raun, ) with high N leaching losses and medium gaseous N losses in farmers’ fields (Christensen, Riley, & Ortiz‐Monasterio, ; Grahmann, Verhulst, Palomino, et al., ). Under gravity irrigated conditions in this area, CA is implemented by using permanent beds (PB) with residue retention, which have the potential to reduce soil degradation and moisture loss, enhance nutrient cycling, decrease greenhouse gas emissions and increase farm sustainability (Verhulst et al., ; Dendooven et al., ).…”
Section: Introductionmentioning
confidence: 99%